Bioadhesive Tannic-Acid-Functionalized Zein Coating Achieves Engineered Colonic Delivery of IBD Therapeutics via Reservoir Microdevices - Khorshid Kamguyan; Rolf Bech Kjeldsen; Saeed Zajforoushan Moghaddam; Melanie Randahl Nielsen; Esben Thormann; Kinga Zór; Line Hagner Nielsen; Anja Boisen (MDPI AG, 2022)
The biggest challenge in oral delivery of anti-inflammatory drugs such as 5-aminosalicylic acid (5-ASA) is to (i) prevent rapid absorption in the small intestine and (ii) achieve localized release at the site of inflammation in the lower gut, i.e., the colon. Here, we present an advanced biopolymeric coating comprising of tannic-acid-functionalized zein protein to provide a sustained, colon-targeted release profile for 5-ASA and enhance the mucoadhesion of the dosage form via a mussel-inspired mechanism. To enable localized delivery and provide high local concentration, 5-ASA is loaded into the microfabricated drug carriers (microcontainers) and sealed with the developed coating. The functionality and drug release profile of the coating are characterized and optimized in vitro, showing great tunability, scalability, and stability toward proteases. Further, ex vivo experiments demonstrate that the tannic acid functionalization can significantly enhance the mucoadhesion of the coating, which is followed up by in vivo investigations on the intestinal retention, and pharmacokinetic evaluation of the 5-ASA delivery system. Results indicate that the developed coating can provide prolonged colonic delivery of 5-ASA. Therefore, the here-developed biodegradable coating can be an eco-friendly substitute to the state-of-the-art commercial counterparts for targeted delivery of 5-ASA and other small molecule drugs.